SOME IMPLICATIONS OF THE PROBLEM OF AGE AETD GROWTH IN MARINE FISHES FROM THE INDL\N WATERS - Qasim, S Z (Indian Journal of Fisheries, 2011)
Growth studies on teleosts from the Indian waters are largely based on lengthfrequency distribui ion, for the simple reason that age determination from other conventionalmetjiods has been found to be diflScult. In some fishes, where scales, otoliths andother hard parts show clear zonations, it is difficult to conclude that these are formedannually. In all those species, which breed successively over prolonged periods, lengthfrequency distribution will not easily indicate yearly broods. Therefore, it has beensuggested that before undertaking the study on growth, some generalized growthcharacteristics in tropical fishes should be taken into account. Experimental studies onfishes, by keeping them in large cages suspended in the sea, has been suggested as one ofthe possible approaches for determining their rates of growth. The characteristics ofsome of the well-known growth parameters have been described and the various methodsused for estimating the mortality rates of fishes have been indicated. The methodemployed by the Indian workers, for estimating the mortality rate, is to change the sizestructure of the catch into age- structure and then estimate the total instantaneousmortality coeflBcient (z) by comparing the abundance offish at successive ages or from theirnumbers at successive length groups. From the estimate of z, it is possible to determineboth fishing mortality coefficient F and natural mortality coefficient M. The yieldfrom a fishery can be determined by employing the two well-known approaches—theBeverton^Holt approach and Shaefer approach.